Візуальна популяризація Біблії - Огнєва, Олена Дмитрівна; Златогорський, Олексій Євгенович; Ohnieva, Olena D.; Zlatohorskyi, Oleksii Ye. (Інститут народознавства НАН України, 2003)
The paper deals with the problem of the Bibles in the cultural heritage of the Christian civilization. Given in the paper is a brief characteristic of the whole set of the Bible editions in Catholic, Orthodox and Protestant traditions from the post–incunabula books to its contemporaly editions. This set of materials, including the christian icons, the sculptures, works of literature has been presented on “The Bible in the world’ book traditions”, exibition in the Volynian Regional Museum.
The Visual popularization of the Bible
Keywords: Біблія; Волинський краєзнавчий музей; Мартін Лютер; Філіп Меланхтон; Лукас Кранах Молодший; Іона Шліхтінг де Буковець; Еразм Роттердамський; Христофор Фрошауер; Балтазар Моретус; Іоана Меурсім; Іоан Белероз; Генріх Ерташенс; Яков Вуйко